The effect of the interaction between organic and mineral colloids on the availability of some trace elements in some of Iraq’s southern marshes - Hasaneen M. Mahmood1 / Abdulkareem Hasan Odhafa 1 / Hashim H. Kareem2 ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
This study was conducted to ascertain the nature of the presence of organic-mineral complexes and their impact on the availability of some of the trace elements namely copper, iron and manganese in some of Iraq’s southern marshlands. Six pedons were selected for sites for the marshland where the sites included Al-Ahrar. (Wasit governorate) represented by one soil Bedon in Hor al-Delmaj, ALmsharah (Misan Governorate) represented by two soil pedons , the first is located in Hur Al-Azim 1, the second in Hur Al-Sanaf, and the Al-Kahla (Misan governorate) Represented by one pedon soil located within Hor Umm Na ’aj, and two pedons in AL Kalaat Saleh(Misan governorate) the first is located in Hor Al-Taraba and the second pedon is located in Hor Al-Sodda. The pedons were numbered from 1-6. According to the above sequence, some of the physical and chemical properties of the soil samples of the six pedons were determined, as well as the total and available concentration of studied trace elements (copper, manganese and iron).